2019
DOI: 10.4491/eer.2019.232
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic biochar from alkali-activated rice straw for removal of rhodamine B from aqueous solution

Abstract: To address organic dye wastewater, economic and effective adsorbents are required. Here, magnetic biochar from alkali-activated rice straw (AMBC) was successfully synthesized using one-step magnetization and carbonization method. The alkaline activation caused the large specific surface area, high pore volume and abundant oxygen-containing groups of the AMBC, and the magnetization gave the AMBC a certain degree of electropositivity and fast equilibrium characteristics. These characteristics collectively contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The maximum adsorption capacity of Co/N-mC adsorbent for MO and RhB respectively is 178 mg g −1 and 141 mg g −1 . As listed in Table 1, compared with magnetic porous carbon [33], CMK-3 [34], magnetic biochar [35], N-doped carbons [36] and other types of adsorbents [37][38][39], Co@N-mC composites presented higher adsorption activity for RhB or MO. The adsorption capacity over Co@N-mC composites was sequenced by MO > RhB might be caused by (1) small sized MO need shorter time but adsorption amount might be increased which the porosity of carbon plays a leading role.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum adsorption capacity of Co/N-mC adsorbent for MO and RhB respectively is 178 mg g −1 and 141 mg g −1 . As listed in Table 1, compared with magnetic porous carbon [33], CMK-3 [34], magnetic biochar [35], N-doped carbons [36] and other types of adsorbents [37][38][39], Co@N-mC composites presented higher adsorption activity for RhB or MO. The adsorption capacity over Co@N-mC composites was sequenced by MO > RhB might be caused by (1) small sized MO need shorter time but adsorption amount might be increased which the porosity of carbon plays a leading role.…”
Section: Resultsmentioning
confidence: 99%
“…The information mentioned above suggested that uptake of CR would be restricted by the ionic strength. Due to salting out effect resulted from NaCl, CR dissolvability in the aqueous solution decreased, which may lead to the agglomeration of CR, and then hydrophobicity of CR increased (Fang et al , 2020; Ren et al , 2020). It can be seen from the figure that for the three adsorbents, presence of NaCl exhibited a positive effect on adsorption, and with increasing ionic strength the adsorption capacity of PAn for CR was little influenced and gradually increased.…”
Section: Resultsmentioning
confidence: 99%
“…Biosorption isotherms can represent the interaction between a biosorbate and biosorbent, and provide information about the distribution of the biosorbate between the liquid and solid phases at several equilibrium concentrations. Isotherm modeling is therefore important for biosorption data interpretation and prediction [7,26]. In this study, isotherm models of Langmuir and Freundlich isotherm models were used to interpret the experimental isotherm data of RCS.…”
Section: Isothermsmentioning
confidence: 99%